2022
DOI: 10.1051/ro/2022046
|View full text |Cite
|
Sign up to set email alerts
|

Decision and coordination analysis of extended warranty service in a remanufacturing closed-loop supply chain with dual price sensitivity under different channel power structures

Abstract: This paper studies the impact of dual price sensitivity (product price sensitivity and extended warranty service price sensitivity) on the decision of the closed-loop supply chain(CLSC) where manufacturers are responsible for recycling and providing extended warranty service under different channel power structures. First, the dynamic game model is used to describe the three channel power structure models of centralized (C), Manufacturer-led Stackelberg (MS), and Retailer-led Stackelberg (RS); then mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Findings from the research of Arti, et al (2022) also show that before consumers make purchase decision, consumers first compare several alternative choices. This is also in line with the research findings of Zhu et al (2022) who found that price has a positive effect on consumer purchase decision. Several other studies have determined that prices have a positive effect on consumer purchase decision, including: Henao, et all (2022); Pradana, et all (2022).…”
Section: Purchase Decisionsupporting
confidence: 92%
“…Findings from the research of Arti, et al (2022) also show that before consumers make purchase decision, consumers first compare several alternative choices. This is also in line with the research findings of Zhu et al (2022) who found that price has a positive effect on consumer purchase decision. Several other studies have determined that prices have a positive effect on consumer purchase decision, including: Henao, et all (2022); Pradana, et all (2022).…”
Section: Purchase Decisionsupporting
confidence: 92%
“…The highly significant quadratic price effects found in the multilogit model showing that the concern of the authors is well justified. The discovery contradicts what was typically specified in the pricing analytical model (Zhou and Duan, 2022; Zhu et al. , 2022) where the online and offline prices are assumed to affect the demand linearly.…”
Section: Resultsmentioning
confidence: 64%
“…The highly significant quadratic price effects found in the multilogit model showing that the concern of the authors is well justified. The discovery contradicts what was typically specified in the pricing analytical model (Zhou and Duan, 2022;Zhu et al, 2022) where the online and offline prices are assumed to affect the demand linearly. It also contrasts the findings of empirical studies (Hu and Tracogna, 2020;Lee et al, 2020), where the linear relationship is usually used to describe the relationship between price and the WTP (or channel preferences).…”
Section: Description Of the Numerical Examplementioning
confidence: 69%
“…Li et al (2021a, b) explored the effect of channel power structure and government subsidy scheme on the supply chain profit and the innovation investment. Zhu et al (2022) explained the impacts of power structure, remanufacturing cost saving and dual price sensitivity on a closed-loop supply chain, where the manufacturer is responsible for collecting used products and providing extended warranty service. Wu et al (2022) discussed the strategic interaction of the manufacturer's credit payment services and the channel power structure on the dual-channel supply chain.…”
Section: Power Structure In Supply Chainsmentioning
confidence: 99%